ENHANCING VOCABULARY MASTERY OF THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 2 PALEMBANG THROUGH SUBTITLED MOVIES - Wahid Ibrahim (Jurnal Dosen Universitas PGRI Palembang)
ABSTRAKThe objectives of this study were to find out whether or not the use of subtitled movies could (1) enhance students‟ vocabulary achievement; and (2) difference in the tenth graders‟ vocabulary achievement between who were though by using subtitled movies and those who were not. The sample of the study was all tenth grade students of SMA Muhammmadiyah 2 Palembang in the academic year of 2013/2014 that consisted of 71 students. A quasi-experimental design was used in this research with 20 meetings including pre-test and post-tests. The findings showed that (1) there was a significant difference in thetenth graders‟ vocabulary mastery after they are taught using subtitled movie. (2) Using subtitled movie as a medium could enhance vocabulary mastery. (3) Using subtitled movie or audio visual as medium to teach English provide the students more fun in teaching learningactivity. To show the value of the results of this research, some interpretations are presented and conclusions are drawn.Key Words: Subtitled Movies, Vocabulary Mastery